2016
DOI: 10.1007/978-3-319-47437-3_96
|View full text |Cite
|
Sign up to set email alerts
|

Welcome to the Future – How Naïve Users Intuitively Address an Intelligent Robotics Apartment

Abstract: Abstract. The purpose of this Wizard-of-Oz study was to explore the intuitive verbal and non-verbal goal-directed behavior of naïve participants in an intelligent robotics apartment. Participants had to complete seven mundane tasks, for instance, they were asked to turn on the light. Participants were explicitly instructed to consider nonstandard ways of completing the respective tasks. A multi-method approach revealed that most participants favored speech and interfaces like switches and screens to communicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…Moreover, especially naïve Japanese participants reported problems completing the study as they felt they lacked knowledge of robots and thus did not feel competent to evaluate a robot's design. Similarly, in a HRI study situated in an intelligent robotics apartment, [49] found that participants were not willing to interact with a robot because they did not feel competent to judge its capabilities. This previous research revealed participants' need for detailed information about a robot's functions before HRI could successfully be initiated.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, especially naïve Japanese participants reported problems completing the study as they felt they lacked knowledge of robots and thus did not feel competent to evaluate a robot's design. Similarly, in a HRI study situated in an intelligent robotics apartment, [49] found that participants were not willing to interact with a robot because they did not feel competent to judge its capabilities. This previous research revealed participants' need for detailed information about a robot's functions before HRI could successfully be initiated.…”
Section: Discussionmentioning
confidence: 99%
“…This previous research revealed participants' need for detailed information about a robot's functions before HRI could successfully be initiated. A lack of information and experience with robots might cause feelings of insecurity (see [49]). To feel safe, people want to control a technical system such as a robot any time (see [40], [49]).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…People may have difficulties in realizing whether a robot is ready for interaction, especially when it is stationary [ 53 ]. A robot can actively interact with objects and humans using social cues [ 54 ].…”
Section: Literature Reviewmentioning
confidence: 99%